2008
DOI: 10.1016/j.adolescence.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Interaction between social class and risky decision‐making in children with psychopathic tendencies

Abstract: Objective-Adult psychopaths are thought to have risky decision-making and behavioral disinhibition, but little is known about themoderating effects of psychosocial factors and whether these associations can be observed in children with psychopathic tendencies. This study tests the biosocial hypothesis that social class will moderate psychopathy-neurocognition relationships, with these effects being stronger in children fromhigh social classes.Method-Preadolescent community twins (N = 298) were assessed on deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
4
21
0
2
Order By: Relevance
“…Previous studies have used the IGT to assess decision making in children and adolescents with ADHD [21], psychopathic tendencies [22], and self-harm tendencies [23]. One difference from the original task was that play money was converted from U.S. dollars to Japanese yen [24].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have used the IGT to assess decision making in children and adolescents with ADHD [21], psychopathic tendencies [22], and self-harm tendencies [23]. One difference from the original task was that play money was converted from U.S. dollars to Japanese yen [24].…”
Section: Methodsmentioning
confidence: 99%
“…In those terms, they argue that the circuitry underlying reward processing (orbitofrontal cortex—OFC) develops earlier than the other circuits of the prefrontal cortex, and thus SES would have a smaller impact over emotional cognition. Furthermore, while some studies have found SES factors to be significantly associated with performance on complex decision-making tasks in pre-adolescents (Gao et al, 2012) and with a delay of gratification task in adolescents (Anokhin et al, 2011) and adults (Green et al, 1996), other studies failed to find such association in kindergarteners (Noble et al, 2005), school-aged children (Noble et al, 2007), and adolescents (Olson et al, 2007). …”
Section: Introductionmentioning
confidence: 97%
“…For example, using the Iowa Gambling Task, several studies have found that while nonpsychopathic individuals learned to avoid “risky” decks, psychopaths made more risky decisions over time, indicating their inability to guide behavior based on somatic markers (Blair, Colledge, & Mitchell, 2001; Mitchell, Colledge, Leonard, & Blair, 2002; van Honk, Hermans, Putman, Montagne, & Schutter, 2002). However, some have failed to find this relationship (Blair & Cipolotti, 2000), or have found that the relation is moderated by attention, anxiety, or social status (Blair & Cipolotti, 2000; Gao, Baker, Raine, Wu, & Bezdjian, 2009; Lösel & Schmucker, 2004; Schmitt, Brinkley, & Newman, 1999). Using a different paradigm, Raine and colleagues (Ishikawa, Raine, Lencz, Bihrle, & LaCasse, 2001; Raine, Lencz, Bihrle, LaCasse, & Colletti, 2000) have provided additional supporting evidence.…”
mentioning
confidence: 99%